The discovery of three hot Jupiters, NGTS-23b, 24b, and 25b, and updated parameters for HATS-54b from the Next Generation Transit Survey. Issue 4 (9th November 2022) - Jackson, David G; Watson, Christopher A; de Mooij, Ernst J W; Acton, Jack S; Alves, Douglas R; Anderson, David R; Armstrong, David J; Bayliss, Daniel; Belardi, Claudia; Bouchy, François; Bryant, Edward M; Burleigh, Matthew R; et al.
ABSTRACT: We report the discovery of three new hot Jupiters with the Next Generation Transit Survey (NGTS) as well as updated parameters for HATS-54b, which was independently discovered by NGTS. NGTS-23b, NGTS-24b, and NGTS-25b have orbital periods of 4.076, 3.468, and 2.823 d and orbit G-, F-, and K-type stars, respectively. NGTS-24 and HATS-54 appear close to transitioning off the main-sequence (if they are not already doing so), and therefore are interesting targets given the observed lack of hot Jupiters around sub-giant stars. By considering the host star luminosities and the planets' small orbital separations (0.037–0.050 au), we find that all four hot Jupiters are above the minimum irradiance threshold for inflation mechanisms to be effective. NGTS-23b has a mass of 0.61 M J and radius of 1.27  R J and is likely inflated. With a radius of 1.21  R J and mass of 0.52 M J, NGTS-24b has a radius larger than expected from non-inflated models but its radius is smaller than the predicted radius from current Bayesian inflationary models. Finally, NGTS-25b is intermediate between the inflated and non-inflated cases, having a mass of 0.64 M J and a radius of 1.02  R J . The physical processes driving radius inflation remain poorly understood, and by building the sample of hot Jupiters we can aim to identify the additional controlling parameters, such as metallicity and stellar age.